2009
DOI: 10.1021/bi9004478
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of a Lutein-Binding Protein from Human Retina

Abstract: Dietary intake of lutein and zeaxanthin appears to be advantageous for protecting human retinal and macular tissues from degenerative disorders such as age-related macular degeneration. Selective concentration of just two of the many dietary carotenoids suggests that uptake and transport of these xanthophyll carotenoids into the human foveal region are mediated by specific xanthophyll-binding proteins such as GSTP1 which has previously been identified as the zeaxanthin-binding protein of the primate macula. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 42 publications
1
88
0
Order By: Relevance
“…Taken with the previous reports of heritability in excess of 70%, these findings suggest that genetic factors exert an overwhelming influence on the amount of MP that is deposited in the eye. Given that several specific xanthrophyll-binding proteins have been identified, 38,39 including the Pi isoform of gluthathione S-transferase, 38 it is possible that specific polymorphisms may exist that influence the uptake, metabolism or deposition of L and Z. Indeed, genetic factors are likely to account for part of the variance unaccounted for in studies investigating the relationships between dietary, serum, and macular carotenoid concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken with the previous reports of heritability in excess of 70%, these findings suggest that genetic factors exert an overwhelming influence on the amount of MP that is deposited in the eye. Given that several specific xanthrophyll-binding proteins have been identified, 38,39 including the Pi isoform of gluthathione S-transferase, 38 it is possible that specific polymorphisms may exist that influence the uptake, metabolism or deposition of L and Z. Indeed, genetic factors are likely to account for part of the variance unaccounted for in studies investigating the relationships between dietary, serum, and macular carotenoid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study that looked specifically at the spatial profile of MP using dual-wavelength analysis of autofluorescence images found that a ring-like structure of MP was present in almost 20% of the participants, tended to be bilateral and was significantly more common in females and never smokers. 40 Although substantial progress has been made in understanding mechanisms involved in the uptake, metabolism, and deposition of L and Z, 39,41 it is clearly a complex process. The ratio of L/Z/meso-zeaxanthin varies with retinal profile with Z predominant at the central peak and L predominant in the peripheral retina.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody to B. mori CBP has cross-reactivity to macular carotenoid transporter identified from human retina and layers of the primate macula where the macular carotenoid pigment is at its highest concentration (15). The human macular carotenoid transporter StARD3 (also known as MLN64) was discovered by Bernstein et al in 2009 (16).…”
Section: The Human Macular Carotenoid Transporter Discovered Using Anmentioning
confidence: 99%
“…Bhosale et al characterized a zeaxanthin-binding protein Pi isoform of human glutathione S-transferase (GSTP1) (26). Steroidogenic acute regulatory domain 3 (stARD3) was identified as a lutein-binding protein (27,28). stARD was shown to be expressed in mitochondria (29).…”
Section: Discussionmentioning
confidence: 99%